Two axis solar tracker based on solar maps, controlled by a low-power microcontroller - Duarte, Francisco (2019)
There are actually several solutions for two axis solar tracking systems using electromechanical devices, in which a controller detects the Sun apparent position, and controls the position of the structure supporting the panels toward the sun by enabling the engines movement. This work studies the solution of two axis solar tracking system based on solar maps, which can predict the exact apparent position of the Sun, by the latitude's location, thereby avoiding the need to use sensors or guidance systems. To accomplish this, it is used a low-power microcontroller, suitably programmed, to control two electric motors to ensure that the panels supporting structure is always oriented towards the sun.